Persepsi Pasien terhadap Terapi Akupresur dalam Mengatasi Insomnia di Sebuah Klinik Kota Semarang - Varrela Salsabila Imawan; Fadly Husain (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2024)
Insomnia is one of the sleep disorders in the form of difficulty in starting sleep, difficulty maintaining sleep and sleep satisfaction. In an effort to overcome this problem, acupressure alternative treatment can be the choice of patients with chronic sleep disorders to help improve sleep quality and reduce the negative impact of insomnia on health. Acupressure treatment is an alternative treatment that involves applying pressure to certain points on the body using a blunt object such as a wooden stick. The acupressure massage points in overcoming insomnia are GV29 (bridge of the nose), EX-HN1 (the back of the head), and EX-HN5 (temples). This study aims to find out the massage method of acupressure treatment in overcoming insomnia in patients with chronic sleep disorders and to find out the perception of patients with chronic sleep disorders regarding alternative treatment of acupressure massage. The research method used in this study is a descriptive qualitative approach and uses the disease theory system proposed by Foster and Anderson. The results of the study show that acupressure treatment can be one of the alternative non-medical treatments that can deal with the problem of insomnia in the elderly and the perception of the elderly regarding acupressure treatment can be varied, seen from the patient's subjective experience, the patient's interests and beliefs, and the patient's body response.